Biomimetic Design for Enhanced Thermal Performance of Vapor Chambers - Jingyu Shen; Ce Guo (Energies)
Vapor chambers (VCs) are efficient heat spreaders that rely on wicks to realize the circulation of a phase-changing working liquid and can be used to address heat dissipation problems in electronic devices, aerospace, and satellite equipment. In this study, we propose a novel vapor chamber with biomimetic wick structures and composite lattice supports to enhance the thermal management and load-bearing performance of vapor chambers. The experiments and COMSOL multiphysics 6.1 simulation results indicate that the biomimetic design can improve the startup performance, thermal management, and load-bearing performance of the VC. Compared to conventional VCs, at a filling ratio of 20% the biomimetic VC reduces the time to reach a steady state by 11.7% and improves the uniformity of temperature by 7.74%. This study provides a novel design concept for VCs and verifies the operating performance of vapor in high heat flux density cases, providing a reference for the innovative design and enhanced heat transfer of phase change-based thermal management equipment.